2014
DOI: 10.2147/ndt.s68039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of stress in junior doctors during their internship training: a cross-sectional study of three Saudi medical colleges’ hospitals

Abstract: BackgroundMedical science is perceived as a stressful educational career, and medical students experience monstrous stress during their undergraduate studies, internship, and residency training, which affects their cognitive function, practical life, and patient care. In the present study, an assessment of the prevalence of self-perceived stress among new medical graduates during their internship training has been performed, and correlations of self-perceived stress with sex, marital status, and clinical rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 49 publications
3
66
2
6
Order By: Relevance
“…É crescente a busca do entendimento desse processo, da compreensão de suas causas e consequências. O tema tem sido alvo de diversas pesquisas [9][10][11][12][13][14] , e a elucidação dos agentes estressores é considerada fundamental para a compreensão da gênese do estresse, a fim de que possam ser aplicadas medidas que minimizem ou reduzam o problema.…”
Section: Introductionunclassified
“…É crescente a busca do entendimento desse processo, da compreensão de suas causas e consequências. O tema tem sido alvo de diversas pesquisas [9][10][11][12][13][14] , e a elucidação dos agentes estressores é considerada fundamental para a compreensão da gênese do estresse, a fim de que possam ser aplicadas medidas que minimizem ou reduzam o problema.…”
Section: Introductionunclassified
“…Burnout can cause errors in judgment leading to poor patient care outcomes 11 . Several studies have shown that the level of stress and depression are higher among intern house officers 12 . One study has shown that nearly 73.0% of intern house officers were under stressed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The high societal expectations on students to perform various undefined, inconsistent, and unachievable roles in the present socio-cultural, economic, and bureaucratic contexts of the society cause heavy stress on students (Lal, 2014). Studies revealed that students experience a relatively high level of personal distress with adverse consequences on academic performance, competency, professionalism, and health (Abdulghani et al, 2011;Abdulghani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%